Experimental and numerical studies on hysteretic behavior of all-steel bamboo-shaped energy dissipaters. (15th June 2018) - Wang, Chun-Lin; Liu, Ye; Zhou, Li
Highlights: An all-steel bamboo-shaped energy dissipater (SBED) was investigated. SBED has stable hysteretic behavior and controlled deformation patterns. Geometrical parameters have significant influence on SBED. Failure modes are related to bending deformation, stress concentration and torsion. Recommended β values are given at different strain amplitudes. Abstract: Energy dissipaters constructed in precast structures play an important fuse-type role in concentrating damage and protecting the primary structure. The stable hysteretic behavior, easy fabrication and low cost are expected characteristics for high-performance energy dissipater. In this paper, an all-steel bamboo-shaped energy dissipater consisting of an inner bamboo-shaped core and an outer restraining tube was developed, which aimed at guaranteeing the performance of the energy dissipater under relatively high strain amplitude and avoiding the adverse effect of grouting and welding. Parametric studies on geometrical variables were performed to investigate the low-cycle fatigue behaviors and deformation patterns of the proposed bamboo-shaped dissipaters. Test results showed that all-steel bamboo-shaped dissipaters showed stable hysteretic curves and no local or overall buckling were observed. Failure modes of bamboo-shaped energy dissipater were affected by the lateral deformation resulted from bending, stress concentration around the fillet and the torsion in the segment. The torsion, contact conditions and the wavelength were discussed via finite element analyses and theoretical derivations.